Model Koordinasi Rantai Pasok Berbasis Kemitraan Syariah: Analisis Efisiensi dan Keadilan Bagi Pemasok dan Produsen - Andrian Anwar L Nata (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2026)
This study aims to design and analyze a supply chain coordination model based on Sharia principles, focusing on its impact on operational efficiency and fairness in the relationship between suppliers and producers. The research uses a mixed-method approach combining quantitative and qualitative analysis, with data collected from 96 business units in West Java and Central Java. Data Envelopment Analysis (DEA) and regression analysis are applied to measure efficiency and test the influence of the partnership model. The results show that the conventional transactional system only achieves an efficiency score of 0.671 and a fairness index of 37.6, while the Sharia-based partnership model reaches 0.912 in efficiency and 84.8 in fairness. The model, which combines Musyarakah and Wakalah contracts, significantly reduces transaction costs, shortens delivery time, and ensures balanced sharing of risks and profits. This study confirms that Sharia principles provide a viable framework to build a supply chain system that is not only economically efficient but also fair and sustainable for all parties involved.